Variation in Electron Radiation Properties Under the Action of Chirped Pulses in Nonlinear Thomson Scattering - Jiachen Li; Junyuan Xu; Zi Wang; Qianmin Zheng; Juncheng Yan; Youwei Tian (Applied Sciences)
This paper primarily focuses on the changes in electron motion trajectories, radiation spatial distribution, radiation spectra, and time spectra under the combined influence of pulse width and chirp parameters. It discusses the motion characteristics of electrons in Gaussian circularly polarized laser-chirped pulses with different chirp parameters and pulse widths. This study examines the asymmetry in radiation distribution, the increase in peak power, the time adjustment in main peak generation, and the coupling effects of spatial distribution under the combined action of pulse width and chirp parameters. It also explores the similarity between chirp effects and pulse broadening. Overall, this paper provides an important reference for further understanding and applying chirped pulses in optics and physics by deeply studying the characteristics of electrons under varying conditions of chirp parameters and pulse widths.